A Systematic Literature Review of Quality Seven Tools - Barata Sutrisno (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2022)
Basic quality seven tools help any organizations to improve their capability and process to fit into update situation and condition base on optimum choice they can select, in first step data need to be collected over the time upon agreed to get baseline data, as a visually how often data will emerge is a important also to compile it into some interactive graph of variations, if there any analysis can made and resulted as a listed problem occur from process have been finished, we can grade it as well to see which one impactful to our process and will be the top priority to improve, and this paper is targetted to see is the seven tools of quality is the comprehensive tools that can figured out any result that bridge us to varius group of result and easy to determine any conclution to make improvement for future plan tahat create continuous significant optimization to sustainability process to help any industry acheive a good analysis to growth over the years to come.